Poverty among the small-scale plantation holders - Saifullah, Md Khaled; Kari, Fatimah; Othman, Azmah (Emerald, 2018)
Purpose – The purpose of this paper is to study the socio-economic condition of indigenous households involved in the production of palm oil and natural rubber in Peninsular Malaysia. Design/methodology/approach – Discriminant analysis is used in this study. Findings – This study finds that 49.70 percent of natural rubber plantation owners and 37.3 percent of the palm oil plantation owners live under the national poverty line. Discriminant analysis shows that natural rubber plantation size has a significant difference between income below the poverty line and above the poverty line. But palm oil plantation size is not significantly different between income below and above the poverty line, mainly because small-scale palm oil farms receive help from the government and other agencies. This study also finds that the majority of indigenous people do not have ownership rights to their land. Practical implications – This study suggests that small-scale plantation holders should be provided with training to upgrade their skills to increase productivity. Furthermore, finding an appropriate land ownership model helps to understand the fundamental issue of poverty among the small-scale plantation holder of indigenous people in Peninsular Malaysia. Originality/value – Primary data are used in this study. The results show different scenarios than the existing studies.